Metodical experts of detection of content of tar substances in fuels for jet engines - Соловьев, A. M.; Кузнецова, О. Я. (Proceedings of National Aviation University (archive), 1998)
Given are the results of research of influence of fuel composition components on the magnitude of magnetooptical activity. It was established that the hydrocarbon composition of fuel does not influence on the magnetooptical activity of tars and is determined only by their concentration. This method allows to find the content of tars in any type of fuel